Relasi Kaidah Fiqih dengan Konsep Mas?Lah?ah? sebagai ‘Illat Hukum - Moh. Dliya'ul Chaq (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2014)
Pattern formulation of rules of jurisprudence to find points of unity in jurisprudence existing products together with qiyâs pattern, a pattern similar to the pattern even qiyâs position and function yet still debated scholars. Become more attractive especially when some scholars claim that the whole issue of jurisprudence back on one thing rather than on, the rule was interesting mas?lah?ah, while the mas?lah?ah beneficiaries according to some scholars can be used as a source or illat law. Through content analysis models interactif and with literature data found; was mas?lah?ah has a strong relationship with the rules of fiqh concretely; the rules of fiqh is equivalent to illat law because the rules of fiqh is the point of unity of a cross section of various products in the form of jurisprudence meaning kullî of some legal juz’i, in which juz’i law derived from the Qur’an, hadîth, ijmâ’, and qiyâs order to maintain the benefit of the people in the world and the hereafter, and because of the rules of fiqh is the one mas?lah?ah itself where mas?lah?ah the one can be used as a illat if established, supported and demonstrated by nas?s? and do not contradict nas?s?.